The Role of Education and Family Background in Marriage, Childbearing and Labor Market Participation in Senegal - Francesca Marchetta; David E. Sahn (Institute for the Study of Labor (IZA), 2015)
This paper examines the role of education and family background on age at marriage, age at first birth, and age at labor market entry for young Senegalese women. We use a multiple-equation framework that allows us to account for the endogeneity that arises from the simultaneity of the four decisions that we model. Our results highlight the importance of a woman's own education in delaying marriage, and that the relationship between her education and the timing of childbearing and of entering the labor market mainly operates through the influence of schooling decisions on the age at marriage. We show that marriage and motherhood decisions are interrelated and that the timing of first birth strongly depends on the duration of marriage. We also shed light on the composite influence of parental education and death shocks on all the outcomes we examine.
Keywords: O12; I25; J12; J13; 330; duration models; multiple equations; unobserved heterogeneity; Senegal